2009
DOI: 10.1099/vir.0.012872-0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous tumour development in human papillomavirus type 8 E6 transgenic mice and rapid induction by UV-light exposure and wounding

Abstract: Cutaneous human papillomavirus type 8 (HPV8) is carcinogenic in patients with epidermodysplasia verruciformis. Transgenic mice with the complete early region (CER) of HPV8 spontaneously developed papillomas, dysplasia and squamous cell carcinomas of the skin. To characterize the role of individual early genes in carcinogenesis, the E6 and E6/E7 genes were expressed separately in transgenic mice. Nearly all HPV8-E6-positive mice spontaneously developed multifocal tumours, characterized by papillomatosis, hyperk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
123
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(134 citation statements)
references
References 45 publications
5
123
1
5
Order By: Relevance
“…Synergy between βPV and UVR has also been documented in animal models. In transgenic mice expressing the HPV8 early region or E6 gene alone, a single dose of UVR rapidly promoted papillomas and cSCC formation,16 and in HPV38 E6/E7 transgenic mice, UVR also induced the development of actinic keratoses and cSCC 17. Certain βPV types also appear to have enhanced replication in the context of host immunosuppression, likely accompanied by increased oncogene expression and oncogenic activity 44…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synergy between βPV and UVR has also been documented in animal models. In transgenic mice expressing the HPV8 early region or E6 gene alone, a single dose of UVR rapidly promoted papillomas and cSCC formation,16 and in HPV38 E6/E7 transgenic mice, UVR also induced the development of actinic keratoses and cSCC 17. Certain βPV types also appear to have enhanced replication in the context of host immunosuppression, likely accompanied by increased oncogene expression and oncogenic activity 44…”
Section: Discussionmentioning
confidence: 99%
“…αHPVs (eg, mucosal HPV types 16 and 18) are responsible for the development of cervical carcinoma and other mucosal SCCs, including anogenital and oropharyngeal carcinomas 10. The role of skin βPVs in cSCC carcinogenesis is controversial,9, 11, 12 but evidence for etiologic involvement is accumulating 13, 14, 15, 16, 17. βPV cause latent, persistent skin infections18 and were first discovered in cSCCs from patients with epidermodysplasia verruciformis, a rare genetic skin disease characterized by increased susceptibility to βPV with a high risk of cSCC on sun‐exposed skin 9…”
Section: Introductionmentioning
confidence: 99%
“…Synergy between keratinocyte activation during wounding and targeting of b 1 -integrin by E6 may have implications for previous observations of increased papilloma formation upon wounding of transgenic HPV8 E6 mice (Marcuzzi et al, 2009). Therefore, targeting of b 1 -integrin by high-risk cutaneous E6 proteins with the YHDW motif might contribute to the higher propensity of malignant conversion upon infection with high-risk b-HPV.…”
Section: Discussionmentioning
confidence: 86%
“…E6 proteins encoded by b-HPVs do not in general share this function; however, a recent report suggested that the HPV49 E6 protein is able to target p53 for degradation to some degree (Cornet et al, 2012), but whether this is dependent on the p53 isoform (Storey et al, 1998), as noted previously for specific mutants of HPV5 E6 (Simmonds & Storey, 2008), remains to be determined. Nevertheless, transgenic mice expressing the HPV8 E6 protein mimic expression of the complete early region of the HPV8 genome, in that E6 expression leads to papilloma formation, which can progress spontaneously to SCC (Marcuzzi et al, 2009). Therefore, b-HPV E6 proteins have tumorigenic potential independent of the degradation of p53.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation